2016
DOI: 10.18203/issn.2454-5929.ijohns20160954
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fine needle aspiration biopsy in parotid gland neoplasm

Abstract: <p class="abstract"><strong><span lang="EN-US">Background: </span></strong>The value of fine needle aspiration biopsy (FNAB) in the diagnosis of parotid masses remains unclear, considering current literature. The surgical procedure is not planned according to the FNAB results by the majority of the otorhinolaryngologists. Objectives of the study was to compare the results of FNAB and histopathological results in diagnosing malignancy and benign lesions of parotid gland and to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
1
2
0
5
Order By: Relevance
“…Similar distributions of the tumor were noted in various studies. 9,14,16 The present study demonstrated sensitivity of 78.57% and specificity as 96.96%. The positive and negative predictive values were found to be 91.60% and 91.40% respectively.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Similar distributions of the tumor were noted in various studies. 9,14,16 The present study demonstrated sensitivity of 78.57% and specificity as 96.96%. The positive and negative predictive values were found to be 91.60% and 91.40% respectively.…”
Section: Discussionsupporting
confidence: 63%
“…The main reason for these false negative results may be sampling errors, observational errors, underassessment of low-grade tumors due to their bland cytological features. 9 In the current study, there were 3 false negative cases which are listed above.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Tükürük bezi tümörleri, baş boyun tümörlerinin sadece %2-3 ' ünü oluşturmaktadır (2). Bu tümörler, tükürük bezlerinin bulunduğu her alanda görülebilmesine rağmen, en sık olarak parotis bezinde görülmektedir (3). Literatürde, tanımlanmış çok sayıda histopatolojik tükürük bezi tümörü bulunmaktadır.…”
Section: Introductionunclassified
“…-4 cm arasında olanlar için bu oranlar sırasıyla %50, %100, %100, % 80 ve %83.3 idi. Kitle boyutu 4 cm 'den büyük olanlar için bu oranlar sırasıyla %80, %100, %100, %50 ve %83 3. idi.…”
unclassified